Upaya Pemerintah Thailand Dalam Pengembangan Pariwisata Internasional Melalui Festival Budaya Songkran Pada Tahun 2024-2025 - Feny Yolanda Chrismas Sitinjak; Maurin Adelia Putri; Resa Rasyidah (Program Studi S1 Pariwisata, Universitas Muhammadiyah Gorontalo, 2025)
This study examines the role of the Thai government in enhancing international tourism through the Songkran Festival during the 2024–2025 period. Songkran is one of Thailand’s largest cultural festivals and received recognition from UNESCO as an Intangible Cultural Heritage in 2023, providing global legitimacy and strengthening Thailand’s cultural image. This research employs a literature review method by examining academic journals, government reports, international publications, and relevant ASEAN tourism data. The analysis is based on Hari Hartono’s (1974) theory, which outlines four governmental roles in tourism development: coordination with the private sector, infrastructure provision, facility expansion, and general overseas promotion. The findings indicate that the Thai government optimally implements these four roles through collaborations with ICONSIAM and the Jeollanam-do Provincial Government, improvements in transportation infrastructure during the festival period, and the enhancement of public facilities such as security and digital services. In terms of promotion, the Thai government expands its international reach through global campaigns by the Tourism Authority of Thailand (TAT), including a partnership with BBC StoryWorks in the “Amazing Thailand Songkran Festival” program, along with the added international prestige from UNESCO, which further elevates the cultural value and global visibility of Songkran. These findings demonstrate that the government’s strategies effectively boost international tourist arrivals, accelerate post-pandemic recovery, and strengthen Thailand’s soft power